2018
DOI: 10.1029/2018ja025751
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Field Line Eigenfrequencies With Ring Current Intensity

Abstract: We present results from the closed magnetosphere (5.9 ≤ L < 9.5 over all magnetic local times) to demonstrate and assess the variations in field line eigenfrequency with geomagnetic activity. Using the time-of-flight technique with realistic magnetic field and mass density models, the spatial distributions of field line eigenfrequencies are determined for a range of different geomagnetic activity levels, as defined by the Dst index. The results indicate that during geomagnetically active conditions, the eigenf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 95 publications
(154 reference statements)
3
18
1
Order By: Relevance
“…It is important to remember that when using a proxy such as Dst index, two very different intervals are averaged, decreasing Dst during the main phase and increasing Dst during the recovery phase even though both phases pass through the same values of Dst. However, Sandhu, Yeoman, and Rae () model provides useful context for interpreting our results. We now consider the role of the ring current itself in reducing the Alfvén continuum in the inner magnetosphere.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is important to remember that when using a proxy such as Dst index, two very different intervals are averaged, decreasing Dst during the main phase and increasing Dst during the recovery phase even though both phases pass through the same values of Dst. However, Sandhu, Yeoman, and Rae () model provides useful context for interpreting our results. We now consider the role of the ring current itself in reducing the Alfvén continuum in the inner magnetosphere.…”
Section: Discussionmentioning
confidence: 92%
“…Certainly heavy ions must play a role. However, Sandhu, Yeoman, and Rae () constructed a statistical model of the average mass densities as a function of Dst index. Sandhu, Yeoman, and Rae () found that although the average ion mass did increase significantly with increasingly negative Dst index, the electron densities in the inner magnetosphere reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption of a dipole magnetic field configuration may also contribute to discrepancies. During the main phase of a geomagnetic storm, the enhanced ring current significantly distorts and inflates the magnetic field configuration in the inner magnetosphere and field lines with a given footprint latitude can map to larger L values than during non‐storm periods (Ganushkina et al., 2010; Sandhu et al., 2018). The electric field power on the dayside tends to increase with L so the magnetometer measurements would be overestimating values.…”
Section: Discussionmentioning
confidence: 99%
“…Studies, in particular Wharton et al (2020), show that Eigen frequencies across a large range of L values are significantly depressed during the main phase of the storm. This is attributed to a weakening of the local magnetic field strength due to the magnetic field perturbations associated with an enhanced ring current population (Jorgensen et al, 2004;Sandhu et al, 2018), as well as an increase in the local plasma mass density due to enhanced concentrations of heavy ions (e.g., Kale et al, 2009;Kistler & Mouikis, 2016;Sandhu et al, 2017;Yue et al, 2019). Furthermore, studies such as Kale et al (2009), Katus et al (2015) show that during the main phase of the storm the plasmapause boundary moves to lower L values.…”
Section: Why Do Radial Diffusion Coefficients Increase During Storms?mentioning
confidence: 99%